Normal-Weight Central Obesity and Mortality Risk in Older Adults With Coronary Artery Disease - Sharma, Saurabh; Batsis, John A.; Coutinho, Thais; Somers, Virend K.; Hodge, David O.; Carter, Rickey E.; Sochor, Ondrej; Kragelund, Charlotte; Kanaya, Alka M.; Zeller, Marianne; Park, Jong-Seon; Køber, Lars; et al. (Mayo Clinic proceedings, 2016)
To study the relationship between body mass index (BMI) and central obesity and mortality in elderly patients with coronary artery disease (CAD). We identified 7057 patients 65 years or older from 5 cohort studies assessing mortality risk using either waist circumference (WC) or waist-hip ratio (WHR) in patients with CAD from January 1, 1980, to December 31, 2008. Normal weight, overweight, and obesity were defined using standard BMI cutoffs. High WHR was defined as 0.85 or more for women and 0.90 or more for men. High WC was defined as 88 cm or more for women and 102 cm or more for men. Separate models examined WC or WHR in combination with BMI (6 categories each) as the primary predictor (referent = normal BMI and normal WC or WHR). Cox proportional hazards models investigated the relationship between these obesity categories and mortality. Patients' mean age was 73.0±6.0 years (3741 [53%] women). The median censor time was 7.1 years. A normal BMI with central obesity (high WHR or high WC) demonstrated highest mortality risk (hazard ratio [HR], 1.29; 95% CI, 1.14-1.46; HR, 1.29; 95% CI, 1.12-1.50, respectively). High WHR was also predictive of mortality in the overall (HR, 2.14; 95% CI, 1.93-2.38) as well as in the sex-specific cohort. In the overall cohort, high WC was not predictive of mortality (HR, 1.04; 95% CI, 0.97-1.12); however, it predicted higher risk in men (HR, 1.12; 95% CI, 1.01-1.24). In older adults with CAD, normal-weight central obesity defined using either WHR or WC is associated with high mortality risk, highlighting a need to combine measures in adiposity-related risk assessment.